The Effect of International Tourism on the Development of Global Social-Economic Processes - CHERKASOV, Igor Lvovich; SEREDINA, Maria Igorevna; MISHUROVA, Olga Ivanovna; ADASHOVA, Tatiana Alekseevna; LEBEDEVA, Olga Yevgenievna (Journal of Environmental Management and Tourism, 2018)
The purpose of this paper is to analyze the effect of international tourism on the development of global social-economic processes. The authors prove that international tourism not only boosts inflows of foreign currency into the country but also ensures employment for the population and helps make rational use of domestic resources. The paper establishes that international tourism has lately been experiencing exceedingly rapid growth and development, second just to the automotive and chemical industries. Right now, the significance of tourism to the development of global social-economic processes is constantly growing, which is due to the influence of tourism on the economy of various nations. The authors conclude that the development of the tourism industry in various regions may also be fraught with certain dangers, like increased strains on the environment due to excessive concentration of production and people in tourism centers, devalued traditions, and declines in the prestige of national cultures as a result of the commercialization of life.